Development and validation of a questionnaire on EFL teachers attitudes towards classroom observation (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
This study was conducted to construct and validate an EFL teachers attitudes towards classroom observation scale in the context of Iran. For this purpose, one hundred EFL teachers, who were teaching English in Jahan Elm, Institute of Higher Education and Hafez English Language Institute, Mashhad, Iran, were asked to participate in the study and fill in the questionnaire. First, the internal consistency of the instrument as measured by Cronbachs coefficient alpha reliability reached acceptable alpha(s). Then, Confirmatory Factor Analyses (CFAs) were conducted using LISREL 8.80. The results of the CFA as assessed by the CFI/NNFI, RMSEA and chi-x2, reached acceptable fits. The factor structures were defined and the factors were clearly distinguishable from one another. Based on the findings, the researchers concluded that the present scale has undoubtedly strong psychometric characteristics and good construct validity which is useful for assessing EFL teachers views on classroom observation in Iran.